ECOPHYSIOLOGICAL RESPONSE OF NERITA ORYZARUM (RECLUZ), A GASTROPOD, TO VARIATIONS IN TEMPERATURE, pH AND SALINITY - Jaiswar, A. K.; Thakur, M. K.; Kulkarni, B. G. (Journal of Indian Fisheries Association, 2015)
During ecophysiological investigations on an intertidal gastropod, Nerita oryzarum (Reduz), of Mumbai shore, various biochemical changes could be recorded. Glycogen and lipid contents of N. oryzarum were found to decrease, whereas, water content increased with decreasing salinity. The rate of oxygen consumption declined with the decrease in salinity and also in highly acidic (pH 2) as well as highly alkaline (pH 10) sea water. The observed variations in the rate of oxygen consumption and changes in biochemical composition in the animal with changes in salinity, pH and temperature are probably the process of physiological and biochemical adjustments to the fluctuating environmental conditions in the intertidal region. Key words: Ecophysiology, Nerita oryzarum, oxygen consumption